RELATIONSHIP BETWEEN PSYCHOLOGICAL EMPOWERMENT AND ENTREPRENEURIAL SUCCESS AMONG STUDENTS OF HIGHER LEARNING INSTITUTION - Nurwahida Fuad; Abdul Manaf Bohari; Ima Ilyani Ibrahim; Shamshul Anaz Kassim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Basically, entrepreneurship is a decisive factor for today’s economy of knowledge to attain its competitive and dynamic character. It is the engine that propels economic growth and employment creation, while also fostering personal growth and successfully addressing a host of harmful societal issues. Therefore, psychological empowerment emerges as one of the crucial issues in the entrepreneurial success among students of higher learning institution. Increasing psychological empowerment element among students is seen as one of the ways to improve entrepreneurial success and increase the access for economic opportunity after graduation. Since the successful of entrepreneurship among students are still being debated among scholars, therefore the understanding on the concept of psychological empowerment in depth is crucial and requires for further investigation. Therefore, this study was conducted to investigate the role of psychological empowerment that may assist in entrepreneurial success. The total of 327 students from higher learning institution categorised as an entrepreneur in Malaysia participated in this study voluntarily. The time horizon of the study conducted was 2 years. The data was analysed using descriptive and linear regression analysis. The finding obtained from this study indicated that there was significant positive relationship between psychological empowerment and entrepreneurial success. The findings offer evidence that students feel much empowered that lead to entrepreneurial success. This result provides significant impact on knowledge contribution of psychological theories to the entrepreneurial success as well as for entrepreneurship education in higher learning institution.